Thermal-hydraulic design of a double-tube heat exchanger for acetaldehyde heating - Pérez Sánchez, Amaury; Velazco Rosell, Osmani Alberto; Ranero González, Elizabeth; Pérez Sánchez, Eddy Javier (Nexo Revista Científica, 2022)
In the present work, the thermal-hydraulic design of a double tube heat exchanger was accomplished to carry out the heating of acetaldehyde, by using hot water (condensate). A sensitivity study was also carried out to determine the influence of an increase in the acetaldehyde feed rate on six equipment design parameters. The designed heat exchanger will have a total heat transfer area of ​​3.88 m2, an overall fouled heat transfer coefficient of 613.23 W/m2.K, a total number of hairpins equal to three and a cleanliness factor of 0.80. A pumping power of 2.01 W and 5.78 W is required to impulse the acetaldehyde and water, respectively. The six parameters evaluated in the sensitivity study increase with the increment of the acetaldehyde feed mass flow rate. It is concluded that the designed double tube heat exchanger is adequate from the thermal-hydraulic point of view, since the percentage over surface calculated (25.00%) and the pressure drop of both acetaldehyde (1,158.43 Pa) and water (4,550.70 Pa) are below the maximum allowable limit established by the process.